Relationship between socioeconomic status, snomie, and suthoritarianism - Arash Heydari; Ali Teymoori; Hedayat Nasiri; Haghish Ebad Fardzadeh (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2012)
The purpose of the present study is to examine the relationships between socioeconomic status, feeling of anomis, and authoritarianism. Three questionnaires including objectives and subjective dimensions of socioeconomic status,anomie, and authoritarianism were administered on 400 students in Shahid Chamra University, Ahvaz, Iran. results showed significant negative relationship between socioeconomic status and feeling of anomie and authoritarianism. In addition, significant positive relationship was found between anomie and authoritarianism. Regression analyses demonstrated that anomie has a mediation effect on the relationships between socioeconomic status and autoritarianism. These findings suggest that widespread feeling of anomie and authoritarianism in Iran are under influence of socioeconomic status.